Climate policy and the concept of co-benefits in India - Theresa Stahlke (Journal of Social and Economic Development, 2023)
Until the late 1990s, developing countries had perceived the pursuit of development as coming into conflict with the mitigation of climate change. Research showed that mitigation and development can go hand in hand, giving rise to the co-benefits approach. In this paper, the relationship between aiming for development and aiming for climate change mitigation is analyzed from the perspective of the developing country India. While industrialized countries prefer the approach of co-benefits of mitigation, developing countries tend to follow the development-first paradigm with mitigation co-benefits, as a literature and document study show. India had a long way to come from the notion that mitigation was threatening economic growth to adopting the co-benefits approach. The paradigms of "differentiated responsibilities" and of having a right to emit as much as the industrialized countries are deeply rooted. This is also shown by India's reaction to the current economic crisis caused by the COVID-19 pandemic.
Keywords: D63; F53; N4; Q01; Q54; 300; Climate policy; Co-benefits; Developing country; Differentiated responsibilities; India; Mitigation of climate change; NAPCC; Paris agreement; Sustainable development; UNFCCC